Semantic and functional characteristics of Latin American political discourse (a case of El Informador) - I. Iakovenko (Ибероамериканские тетради, 2019)
The research focuses on semantic and functional peculiarities of lexemes libertad, igualdad, justicia, lucha, poder serving to verbalize key concepts of Latin American political discourse and, in particular, the influential Mexican diary El Informador. The investigation is based on the semasiological approach realized in the componential analysis and the semantic-cognitive approach carried out in the conceptual analysis method. The main objectives of the research are: 1)to investigate the semantic structure of the selected units, identify their semes that are regularly implemented in the political discourse; 2)to look for distinctive concepts verbalized by these lexemes; 3) to reveal correspondences between the semes and the concepts studied. The results of the investigation allow us to specify the semantic of the lexemes in the political discourse and justify the use of two fundamentally different approaches for the analysis of the lexical units.